2019
DOI: 10.1016/j.celrep.2019.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analyses of Microbiome and Longitudinal Metabolome Data Reveal Microbial-Host Interactions on Sulfur Metabolism in Parkinson’s Disease

Abstract: SummaryParkinson’s disease (PD) exhibits systemic effects on the human metabolism, with emerging roles for the gut microbiome. Here, we integrate longitudinal metabolome data from 30 drug-naive, de novo PD patients and 30 matched controls with constraint-based modeling of gut microbial communities derived from an independent, drug-naive PD cohort, and prospective data from the general population. Our key results are (1) longitudinal trajectory of metabolites associated with the interconversion of methionine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 74 publications
(124 reference statements)
5
117
0
Order By: Relevance
“…Simulation with FBA concluded that four microbial reactions involved in homoserine metabolism are altered in PD patients, which is consistent with measured levels in plasma of PD patients and homoserine, the precursor of methionine, is part of sulfur metabolism. Furthermore, the authors showed an increase in two bacterial species both involved in sulfur metabolism, B. wadsworthia and A. muciniphila [ 89 ]. Both species have been reported in PD progression [ 90 ].…”
Section: Simulation Of Dysbiosis and Treatment Using Metabolic Networmentioning
confidence: 99%
“…Simulation with FBA concluded that four microbial reactions involved in homoserine metabolism are altered in PD patients, which is consistent with measured levels in plasma of PD patients and homoserine, the precursor of methionine, is part of sulfur metabolism. Furthermore, the authors showed an increase in two bacterial species both involved in sulfur metabolism, B. wadsworthia and A. muciniphila [ 89 ]. Both species have been reported in PD progression [ 90 ].…”
Section: Simulation Of Dysbiosis and Treatment Using Metabolic Networmentioning
confidence: 99%
“…Previously, we have demonstrated the use of personalised metabolic modelling for the stratification of paediatric inflammatory bowel disease patients and controls in a purely in silico approach (Heinken et al, 2019) and validated changes in the metabolome of Parkinson's Disease patients with personalised models built from an unrelated cohort (Hertel et al, 2019). Here, by integrating the AGORA based COBRA community modelling predictions with faecal metabolomics, we could validate our predictions regarding butyrate, glutarate, Fusobacteria and other butyrate producing species.…”
Section: Discussionmentioning
confidence: 75%
“…Higher levels of Akkermansia municiphila stimulate mucin degradation, increasing host susceptibility to IEB disruption. Furthermore, A. municiphila and Bilophila wadsworthia affect sulfur metabolism in PD leading to higher secretion of sulfite, a known neurotoxin causing mitochondrial dysfunction [ 251 ]. In addition, levels of taurine-conjugated bile acids, exploited in the gut lumen as a source of sulfite production, positively associated with scores of clinical severity.…”
Section: Roles Of Diet and Microbiota In Neurodegenerative Diseasementioning
confidence: 99%
“…Meng et al used systemic nutrigenomics to elucidate how ω-3 PUFAs counteract the harmful effects of fructose in brain rats [ 379 ], providing rational support for targeted dietary interventions in humans. Recent studies applying these approaches successfully identified key factors involved in PD pathogenesis [ 251 ]. This hold promises for future applications also in AD and ALS.…”
Section: Future Perspectivesmentioning
confidence: 99%